Study of Lipid Profile in Patients with Diabetes Mellitus Presenting at Tertiary Referral Center in Nepal - K.C., Indu; Deo, Rajeeb K; Roka, Kumar; Singh, Punita; Alam, Zafar (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: Diabetes mellitus is a metabolic disorder associated with dyslipidemia especially in type 2 diabetes mellitus. Lipid abnormalities are associated with increased risk of cardiovascular diseases. The aim of the study was to find out the incidence of dyslipidemia in patients with diabetes mellitus presenting at tertiary referral center of Kathmandu, Nepal. Methods: This was a retrospective study conducted in Medicine and Endocrine OPD of Shree Birendra Hospital, Chhauni, Kathmandu, Nepal after approval from the Institution Review committee. Cases within the period from December 2019 to January 2021 were studied. Data were analyzed using SPSS 21.0. Results: Out of 150 patients with diabetes mellitus, 32.6% had total cholesterol > 200 mg / dl, 60% had elevated LDL, 26.67% patient had elevated TG and 36% patients had low HDL level. Poor glycemic control (HbA1c > 7%) was observed in 86 (57.33%) subjects. Among patients with HbA1c > 9, 3.33% patients had cholesterol > 200, 4.67% patients had TG > 250, 5.33% patients had LDL > 100 and 6.67% patients had HDL < 40. Conclusions: Diabetes mellitus is associated with high incidence of dyslipidemia. The most common pattern observed was elevated level of low-density lipoprotein, cholesterol and triglyceride and low level of HDL. Routine monitoring of lipid profile should be part of patient care.